The Wanderer - Creech, Sharon; Diaz, David (New York Scholastic, 2000)
Thirteen-year-old Sophie and her cousin Cody record their transatlantic crossing aboard the Wanderer, a forty-five foot sailboat, which, along with uncles and another cousin, is en route to visit their grandfather in England.
Keywords: Sailboats -- Fiction; Sailing -- Fiction; Ocean travel -- Fiction; Family life -- Fiction; Grandfathers -- Fiction; Sea stories